2008
DOI: 10.1007/s12217-008-9006-7
|View full text |Cite
|
Sign up to set email alerts
|

The Real-Time Mach-Zehnder Interferometer used in Space Experiment

Abstract: The optical interference method is a promising technique for measuring temperature, density, and concentration in fluids. The non-intrusive and non-invasive nature of its optical techniques to the measured section are its most outstanding features. However, the adverse experiment environment, especially regarding shaking and vibrating, greatly restricts the application of the interferometer. In the present work, an optical diagnostic system consisting of a Mach-Zehnder interferometer (named after physicists Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Moreover, Leppinen [14] showed that curvature effects dramatically dictated the order at which convection influences the core region solutions. Duan et al [15][16][17] used the interference technique and bar line technique to measure surface deformation of buoyant-thermocapillary convection in a rectangular pool. They found that with increasing temperature gradient, surface deformation for h = 3.5 mm and h = 6.0 mm were reversed, and the deformation changes were from several microns to 40 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Leppinen [14] showed that curvature effects dramatically dictated the order at which convection influences the core region solutions. Duan et al [15][16][17] used the interference technique and bar line technique to measure surface deformation of buoyant-thermocapillary convection in a rectangular pool. They found that with increasing temperature gradient, surface deformation for h = 3.5 mm and h = 6.0 mm were reversed, and the deformation changes were from several microns to 40 µm.…”
Section: Introductionmentioning
confidence: 99%
“…According to the theory of information optics and the interference fringes in Mach-Zehnder interferometer [30].…”
Section: Fringe Image Analysismentioning
confidence: 99%